Natural mussel protein-derived antitumor nanomedicine with tumor-targeted bioadhesion and penetration. (February 2023) - He, Yunhong; Wang, Jianwei; Wang, Shuping; Yu, Kaxi; Zhou, Jun; Wang, Jinqiang; Tang, Guping; Gu, Zhen; Bai, Hongzhen
Abstract: Increasing drug infiltration by exerting tumor-specific retention and penetration is a key aspect for antitumor nanomedicine design. Herein, we have developed a mussel adhesive protein-inspired nanomedicine with tumor-targeted adhesion and penetration for enhanced photodynamic therapy and hypoxia-driven chemotherapy. Natural mussel adhesive proteins (NMPs) are conjugated to phenylboronic acid (PBA)-containing Tirapazamine prodrug (PBT) via recognization of DOPA residues of NMPs to PBA moieties of PBT, endowing NMPs with tumor environment-responsive bioadhesion while unaffecting their systematic circulation. Indocyanine green (ICG) is further incorporated into NMPs to acquire nanomedicine ICG-PBT@NMPs with reduced cationic property. In the tumor environment, the cationic property is upturned with the responsive cleavage of DOPA-PBA bonding, facilitating tumor penetration. ICG-PBT@NMPs are then internalized by tumor cells through arginine-transporter endocytosis. Triggered by near-infrared irradiation, ICG-PBT@NMPs generate cytotoxic reactive oxygen species and aggravate tumor hypoxia, which potentiates PBT activation, therefore showing combination antitumor effect in both orthotopic and metastatic breast tumor models. Graphical Abstract: ga1 Highlights: Mussel proteins with intrinsic multifunctionality are used for drug delivery. Engineered mussel proteins are endowed with tumor responsive adhesion. Hypoxia prodrug and photosensitizer are integrated within the protein platform. The bioinspired nanodrug exhibits stealthy circulation and targeted accumulation. The nanodrug exerts antitumor cascade by combining chemo and photodynamic therapy.